Viable alternative in vitro system and comparative metabolite profiling of different tissues for the conservation of ceropegia karulensis - Pandey, M.; Jayaramaiah, R.H.; Dholakia, B.B; Punekar, S.A.; Giri, A.P. (Plant Cell, Tissue and Organ Culture, 2017)
Abstract: Ceropegia karulensis is an endemic and critically endangered plant of the Western Ghats from India. Exploitation of the tubers and poor regeneration from seed has narrowed distribution and propagation of the species. There is a need to develop in vitro propagation methods for C. karulensis to alleviate these problems. Here, we optimized callus induction, somatic embryogenesis and microtuberization from different seedling explants viz. cotyledonary leaf and root. The environmental scanning electron microscopy was used to observe somatic embryonic origin and their developmental stages. Highest callus proliferation was recorded with 2 µM 6-benzylaminopurine and 1 µM 2,4-dichlorophenoxyacetic acid. Somatic embryos derived from cotyledonary leaf explants were more proliferative than root explants. The combination of 2 µM 6-benzylaminopurine, 2 µM naphthalene acetic acid and 7% sucrose in MS media resulted in highest microtuberization. Further, gas chromatography-mass spectrometry based metabolic profiling was carried out from native wild plants and in vitro callus tissues which identified various phytochemicals such as alkaloids, fatty acids, esters alcohols, etc. Multivariate analysis revealed the chemical disparities, where considerable variations were observed between native wild type and in vitro tissues, but no significant differences were found among in vitro callus from both root and cotyledonary explants. Overall, our results suggested that the production of various secondary metabolites found in C. karulensis was not affected by in vitro propagation and could be utilized in the conservation strategies for this plant. Graphical Abstract: [Figure not available: see fulltext.]
Keywords: alkaloids; Metabolites

Retraction: a highly concise and practical route to clavaminols, sphinganine and (+)-spisulosine via indium mediated allylation of α-hydrazino aldehyde and a theoretical insight into the stereochemical aspects of the reaction - Pandey, M.; Chowdhury, P. S.; Dutta, A. K.; Kumar, P.; Pal, S. (RSC Advances, 2019)
A conceptually different approach has been employed for the synthesis of 1,2-amino alcohols by proline-catalyzed α-amination of aldehyde and one-pot indium mediated allylation of the crude α-hydrazino aldehydes. DFT based quantum chemical calculations have been performed to obtain a quantitative explanation of the stereoselectivity of the reaction.